Rainfall-induced Soil Erosion and Sediment Sizes of a Residual Soil under 1D and 2D Rainfall Experiments. (9th May 2016) - Vilayvong, Khonesavanh; Yasufuku, Noriyuki; Ishikura, Ryohei
Abstract: Raindrop impact and surface flow trigger the downstream movement of soil particles by the processes of rainfall-induced soil erosion. A set of laboratory simulated rainfall experiments was carried out to study soil loss and size characteristics of discharged sediments of a soil under a rainfall intensity of 70 mm/h, controlled initial soil suctions and moistures. The rainfall simulation was instrumented with tensiometers and moisture sensors. A new device capable of deriving impact force, velocity, and kinetic energy of a falling waterdrop was developed. Sediment sizes in runoff were characterized by a laser particle size analyzer in order to correlate with the properties of rainfall. 1D simulated rainfall experiments were also employed to study soil detachment and soil susceptibility to rainfall under both saturated and unsaturated soil conditions. The processes of soil erosion and outflow size characteristics of sediments relating to effect of suction were discussed. The proposed set of experiments will be a viable tool for measuring soil loss, sediment runoff, and sediment sizes discharged from a farmland pertaining to properties of rain, soil and flow.